Conservation interventions can benefit species impacted by climate change. (May 2022) - Bowgen, K.M.; Kettel, E.F.; Butchart, S.H.M.; Carr, J.A.; Foden, W.B.; Magin, G.; Morecroft, M.D.; Smith, R.K.; Stein, B.A.; Sutherland, W.J.; Thaxter, C.B.; Pearce-Higgins, J.W.
Abstract: There is an urgent need to quantify the potential for conservation interventions to effectively manage the impacts of climate change on species' populations and ecological communities. In this first quantitative global assessment of biodiversity conservation interventions for climate change adaptation, we identified 77 peer-reviewed studies, including 443 cases describing the response of individual species' populations or assemblages to particular interventions, whilst also accounting for responses to climate change or particular climatic variables. Eighty-two percent of studies were from Europe or North America. In 30% of reported cases, interventions were regarded as beneficial (having a significant positive impact on a population also affected by a climatic variable). However, beneficial outcomes were more likely to be reported when fewer responses were analysed, suggesting a publication bias in the reporting of beneficial responses. Management focused on particular species (e.g. targeted habitat management and species recovery interventions) was modelled to have a higher probability (73%) of being beneficial than more generic interventions such as land and water management (22%) or protection (17%). Although more data on the effectiveness of climate change adaptation for species conservation are required, the diversity of examples reviewed suggests that climate change adaptation can successfully reduce negative impacts of, or enhance positive responses to, climate change. Targeted interventions maximise the persistence of the most vulnerable populations, whilst expanding habitat management and site protection interventions may benefit the largest number of species and ecosystems. The effective monitoring and evaluation of adaptation interventions is required to improve this evidence-base for future decision-making.